Viabilidade técnica e econômica da recuperação energética da biomassa residual da extração do óleo de melaleuca - Tomeleri, João Otávio Poletto (2023)
Among the species of the genus Melaleuca that have secondary metabolites of commercial interest, Melaleuca alternifolia stands out. It is currently the species with the largest areas of cultivation, present in several countries such as Australia, Indonesia, China, Brazil and the United States. Australia has dominated the market for this essential oil since the 1980s, accounting for more than 80% of the total volume traded in the world in 2019. A greater share of Brazil in the cosmetics and pharmaceuticals market would bring benefits such as the generation of direct jobs in the oil production chains and derivative products. The specific aim of this work was to organize relevant information about the main species of the genus Melaleuca, its main botanical characteristics, description of the essential oil market and the distillation techniques applied to obtain the oil. Additionally, tests were carried out to energetically characterize the melaleuca biomass and its residue from the distillation process, in addition to studying possible alternatives for homogenization through the densification of the residual vegetative material. As a general objective, we sought to record the potential of melaleuca cultivation to meet government demands for sustainable development and the establishment of new productive arrangements involving small farmers and traditional communities in the context of the Brazilian bioeconomy. The results obtained in the work demonstrate that the distilled biomass has an aptitude for energy production, with a higher heating value above 4800 kcal.kg-1, and fixed carbon of 19.91%. The main challenges for energy production from this material are its high moisture, which was determined to be 47.13% on a wet basis, influenced by the steam extraction process, and its ash content (4%), which negatively affect the energy efficiency in burning appliances. Additionally, these characteristics hinder subsequent processes of homogenization of the material, such as densification. Controlling both factors, tea tree distillation residues have the potential to be used in thermal conversion and consequently contribute to increasing the economic viability of projects aimed at producing tea tree essential oil in Brazil.